Gambaran Penyakit Jantung Bawaan di Neonatal Intensive Care Unit RSUP Prof. Dr. R. D. Kandou Manado Periode 2013 - 2017 - Manopo, Berry R.; Kaunang, Erling D.; Umboh, Adrian (e-CliniC, 2018)
Abstract: Congenital heart disease (CHD) is a structural heart defect that results from abnormal embryological heart development, or persistence of some parts of the fetal circulation at birth. Congenital heart disease is divided into two categories, namely non-cyanotic congenital heart disease and cyanotic congenital heart disease. Congenital heart disease is caused by interactions between predisposing exogenous factors and endogenous factors. This study was aimed to obtain the profile of CHD in the Neonatal Intensive Care Unit (NICU) of Prof. Dr. R. D. Kandou Hospital Manado in the period 2013 - 2017. This was a retrospective descriptive study using medical record data of patients suffering from CHD in NICU from 2013 to 2017. The results showed that there were 27 patients suffering from CHD consisting of 24 non-cyanotic CHD patients (88.89%) and 3 cyanotic CHD patients (11.11%), and the highest incidence was Atrial Septal Defect (ASD) as many as 17 babies (62.96%). Congenital heart disease was more common in males as many as 18 babies (66.67%). In this study, the clinical symptoms oftenly found was shortness of breath (48.15%) and the most common diagnosis was pneumonia (48.15%). Conclusion: The most common CHD was non-cyanotic CHD. The most commonly found defect was ASD. Clinical symptoms that often arised was shortness of breath, pneumonia was the most common comorbid diagnosis, and the dominant gender of CHD was male.Keywords: non-cyanotic CHD, cyanotic CHD, atrial septal defectÂ Abstrak: Penyakit jantung bawaan (PJB) merupakan defek jantung struktural yang terjadi akibat perkembangan jantung embriologis yang abnormal, atau persistensi dari beberapa bagian dari sirkulasi fetus saat lahir. Penyakit ini dibagi menjadi dua kategori yaitu penyakit jantung bawaan non sianosis dan yang sianosis. Penyakit jantung bawaan disebabkan oleh interaksi antara predisposisi faktor eksogen dan faktor endogen. Penelitian ini bertujuan untuk mendapatkan gambaran penyakit jantung bawaan di Neonatal Intensive Care Unit (NICU) RSUP Prof. Dr. R. D. Kandou Manado periode 2013-2017. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan data rekam medik pasien yang menyandang penyakit jantung bawaan di NICU periode 2013-2017. Hasil penelitian mendapatkan dari 27 pasien dengan PJB, ditemukan PJB non sianotik berjumlah 24 bayi (88,89%) dan PJB sianotik berjumlah 3 bayi (11,11%) dengan angka kejadian terbanyak pada atrial septal defek (ASD) berjumlah 17 bayi (62,96%). Penyakit jantung bawaan paling banyak terjadi pada bayi yang berjenis kelamin laki-laki yaitu berjumlah 18 bayi (66,67%). Gejala klinis yang sering muncul ialah sesak napas (48,15%) dan diagnosis penyerta terbanyak yaitu pnemonia (48,15%). Simpulan: Penyakit jantung bawaan non sianosis merupakan diagnosis terbanyak, jenis ASD, dengan gejala klinis yang sering muncul yaitu sesak napas. Pneumonia merupakan diagnosis penyerta terbanyak. PJB tersering pada jenis kelamin laki-laki.Kata kunci: PJB sianotik, PJB, non sianotik, atrial septal defek